Outcomes of 28(+1) to 32(+0) Weeks Gestation Babies in the State of Qatar: Finding Facility-Based Cost Effective Options for Improving the Survival of Preterm Neonates in Low Income Countries - Parappil, Hussain (Molecular Diversity Preservation International (MDPI), 2010)
In this retrospective study we did a comparative analysis of the outcome of 28(+1) to 32(+0) weeks gestation babies between the State of Qatar and some high income countries with an objective of providing an evidence base for improving the survival of preterm neonates in low income countries. Data covering a five year period (2002–2006) was ascertained on a pre-designed Performa. A comparative analysis with the most recent data from VON, NICHD, UK, France and Europe was undertaken. Qatar’s 28(+1) to 32(+0) weeks Prematurity Rate (9.23 per 1,000 births) was less than the UK’s (p < 0.0001). Of the 597 babies born at 28(+1) to 32(+0) weeks of gestation, 37.5% did not require any respiratory support, while 31.1% required only CPAP therapy. 80.12% of the MV and 96.28% of CPAP therapy was required for <96 hours. 86.1% of the mothers had received antenatal steroids. The 28(+1) to 32(+0) weeks mortality rate was 65.3/1,000 births with 30.77% deaths attributable to a range of lethal congenital and chromosomal anomalies. The survival rate increased with increasing gestational age (p < 0.001) and was comparable to some high income countries. The incidence of in hospital pre discharge morbidities in Qatar (CLD 2.68%, IVH Grade III 0.84%, IVH Grade IV 0.5%, Cystic PVL 0.5%) was less as compared to some high income countries except ROP ≥ Stage 3 (5.69%), which was higher in Qatar. The incidence of symptomatic PDA, NEC and severe ROP decreased with increasing gestational age (p < 0.05). We conclude that the mortality and in hospital pre discharge morbidity outcome of 28(+1) to 32(+0) weeks babies in Qatar are comparable with some high income countries. In two thirds of this group of preterm babies, the immediate postnatal respiratory distress can be effectively managed by using two facility based cost effective interventions; antenatal steroids and postnatal CPAP. This finding is very supportive to the efforts of international perinatal health care planners in designing facility-based cost effective options for low income countries.